Analysis of Bugis Traditional Panai Money in Islamic Perspective Marriages - Anggina Yusila Heryanto; Fatimatuzzahra; Muhibban (Penerbit Hellow Pustaka, 2024)
This study aims to determine the view of Islamic law on Panai Money in Bugis traditional marriage. The research was conducted using a qualitative approach. Based on the results of the research, the Bugis community considers “Panai Money” as an important tradition in their traditional marriage. Although Islam does not specifically regulate Panai Money, it gives freedom (mubah). Islam does not prohibit the giving of Panai Money in the Bugis traditional marriage tradition even though the value of the Panai Money is high because there is no evidence that shows this. Most importantly, the giving of Panai Money should not violate Islamic principles, there is no element of compulsion, according to the ability and ability of the male party.